1968
DOI: 10.1002/aic.690140532
|View full text |Cite
|
Sign up to set email alerts
|

On the narrowing of particle‐size distributions in staged vessels with classified product removal

Abstract: A well-known, but quite inefficient, representation of dead time in a continuous process is that of a series of staged vessels with equal time constants. Buckley (1) compares such a series approximation for dead time, TD, with other methods of dead time representation. The transfer function for this approximation (equivalent to k wellmixed stages in series) is given as The transfer function given by Equation ( 1) , applied to the problem of residence-time distributions of particles residing in a system of k se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1971
1971
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Rapid intermittent withdrawal is considered a form of continuous operation since changes in steady-state conditions are negligible when slurry slug size withdrawn is less than 10% of the crystallizer volume. , Specifically, we study the impact of process parameters including MSMPR temperature and mean residence time on the steady-state product CSD, mean crystal size, and yield. To address the backmixed nature of the MSMPR, different configurations have been employed with the chief aim of obtaining better CSD quality alongside process yield. Attempts to control product CSD using multistage MSMPR crystallizers have been reported in the literature, , and these studies have suggested that the single-stage MSMPR crystallizer is inefficient, because it produces a product with a broader CSD than the multistage MSMPR crystallizer. Also, in terms of process operability, the single-stage MSMPR crystallizer has limited temperature controllability because of its small heat transfer area .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid intermittent withdrawal is considered a form of continuous operation since changes in steady-state conditions are negligible when slurry slug size withdrawn is less than 10% of the crystallizer volume. , Specifically, we study the impact of process parameters including MSMPR temperature and mean residence time on the steady-state product CSD, mean crystal size, and yield. To address the backmixed nature of the MSMPR, different configurations have been employed with the chief aim of obtaining better CSD quality alongside process yield. Attempts to control product CSD using multistage MSMPR crystallizers have been reported in the literature, , and these studies have suggested that the single-stage MSMPR crystallizer is inefficient, because it produces a product with a broader CSD than the multistage MSMPR crystallizer. Also, in terms of process operability, the single-stage MSMPR crystallizer has limited temperature controllability because of its small heat transfer area .…”
Section: Introductionmentioning
confidence: 99%
“…To address the backmixed nature of the MSMPR, different configurations have been employed with the chief aim of obtaining better CSD quality alongside process yield. 25−28 Attempts to control product CSD using multistage MSMPR crystallizers have been reported in the literature, 29,30 and these studies have suggested that the single-stage MSMPR crystallizer is inefficient, because it produces a product with a broader CSD than the multistage MSMPR crystallizer. Also, in terms of process operability, the single-stage MSMPR crystallizer has limited temperature controllability because of its small heat transfer area.…”
Section: Introductionmentioning
confidence: 99%
“…Another advantage of the MSMPR system is its easy conversion from batch processes to continuous processes through the use of simple technologies . Using the mathematical model for MSMPR developed by Randolph and Larson, effective design and configuration of the MSMPR crystallizer to improve product quality has been extensively researched. , Several researchers have reported that the single-stage MSMSR crystallizer is inefficient, because it produces a product with a broader CSD than the multistage MSMPR crystallizer. , In addition, from the view of process operability, the single-stage MSMPR crystallizer is unfavorable, since the temperature controllability is limited, because of its small cooling surface area . This results in a higher operating cost than for the multistage MSMPR crystallizer.…”
Section: Introductionmentioning
confidence: 99%
“…1,11−15 Several researchers have reported that the single-stage MSMSR crystallizer is inefficient, because it produces a product with a broader CSD than the multistage MSMPR crystallizer. 15,16 In addition, from the view of process operability, the single-stage MSMPR crystallizer is unfavorable, since the temperature controllability is limited, because of its small cooling surface area. 17 This results in a higher operating cost than for the multistage MSMPR crystallizer.…”
Section: Introductionmentioning
confidence: 99%